2019
DOI: 10.1371/journal.pone.0213054
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for low birth weight in hospitals of North Wello zone, Ethiopia: A case-control study

Abstract: BackgroundLow birth weight at birth is an important underlying contributor for neonatal and infant mortality. It accounts for nearly half of all perinatal deaths. Identifying predictors of low birth weight is the first essential step in designing appropriate management strategies. Hence, this study aimed to identify risk factors for low birth weight in hospitals of northeastern Ethiopia.MethodsAn institution based case-control study design was conducted from 10th April to 15th December 2016. Three hundred sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
2
23
2
3
Order By: Relevance
“…The prevalence of low birth weight and preterm birth in our study is higher than that reported in other regions of Ghana [42,43], the current 2017 Ghana Maternal Health Survey [44], in Brazil [8,22], and Ethiopia [45]. Low birth weight is a signi cant underlying cause of neonatal and infant mortality in low-and-middle-income countries such as Ghana [44], which implies that participants with low birth weight are at increased risk of neonatal and infant mortality.…”
Section: Discussioncontrasting
confidence: 62%
“…The prevalence of low birth weight and preterm birth in our study is higher than that reported in other regions of Ghana [42,43], the current 2017 Ghana Maternal Health Survey [44], in Brazil [8,22], and Ethiopia [45]. Low birth weight is a signi cant underlying cause of neonatal and infant mortality in low-and-middle-income countries such as Ghana [44], which implies that participants with low birth weight are at increased risk of neonatal and infant mortality.…”
Section: Discussioncontrasting
confidence: 62%
“…In Ethiopia, chewing of khat is becoming habitual and increasing at an alarming rate with an estimated prevalence ranged from 30% to50% (10)(11)(12)(13). According to 2016 Ethiopia Demographic and Health Survey (EDHS), around 27% of men and 12% of women had history of khat chewing (14) with up to 65% during pregnancy (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Khat chewing has different socio-economic, psycho-social, physical and environmental impact (1, 5, 12, 13, 32).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of LBW varies across countries and regions, with higher burden in sub-Saharan Africa and Southeast Asia [ 7 , 8 ]. In Ethiopia, the prevalence of LBW varies across geographical areas, which ranges from 10% to 28% [ 9 12 ]. According to the 2016 Ethiopian Demographic and Health Survey (EDHS), 13% of babies in Ethiopia had LBW [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic factors such as unfavorable socioeconomic conditions, place of residence, age at pregnancy, maternal level of education, and occupation are risk factors for LBW [ 9 , 10 , 15 17 ]. Physical and behavioral characteristics, including low maternal weight at conception, short maternal stature, maternal comorbidities, absence or inadequate prenatal care, unfavorable reproductive history, absence of antenatal care, birth order and interval, multiple pregnancy, and illicit drug use considerably increase the likelihood of LBW [ 12 , 17 20 ].…”
Section: Introductionmentioning
confidence: 99%